Tensile responses of polycrystalline Mo via molecular dynamics simulation: Grain size and temperature effects - Hu, Yiqun; Xu, Jianfei; Su, Lei; Zhang, Yuhang; Ding, Suhang; Shen, Yanhua; Xia, Re (Materials chemistry and physics, 2023)
Polycrystalline Mo has excellent application prospects in micro-nano devices, and its mechanical properties play an essential role in the application. A series of molecular dynamic (MD) simulations has been executed to investigate the mechanical features of monocrystalline and polycrystalline Mo under tensile loading. The influences of mean grain size from 5.00 to 27.10 nm and temperature in the range of 10–1500 K on mechanical parameters are studied. The findings demonstrate that Young's modulus and yield strength increase with mean grain size. For ultimate tensile strength (UTS), the average grain size of 20.43 nm is an inversion point of the relation between UTS and the reciprocal of the square root of mean grain size d−1/2 at 300K. The average shear strain of polycrystalline Mo is higher than that of monocrystalline due to the existence of grain boundaries (GBs). We also found that the mechanical properties, including Young's modulus, UTS, and yield strength, decrease with the increase of temperature. Monocrystalline Mo is more sensitive to temperature than polycrystalline. At high temperatures above 900 K, the mechanical properties of monocrystalline Mo are lower than these of polycrystalline Mo. The results in the present work will accelerate the industrial application of polycrystalline Mo. material science, computational material. [Display omitted] •Tensile behaviors of monocrystalline and nanocrystalline Mo have been studied by MD simulations.•An inversion point of the relation between ultimate tensile strength and d−1/2 is observed.•The transformations that "BCC to FCC to BCC" and the growth of twin bands dominate the deformation of monocrystalline Mo.•The mechanical properties of monocrystalline Mo are more sensitive to temperature than nanocrystalline.